Analisis Pengaruh Partisipasi Masyrakat Kompetensi Aparatur Desa Dan Sistem Pengendalian Internal Terhadap Akuntabilitas Pengelolaan Dana Desa Di Desa Tribur Kecamatan Abad Selatan Kabupaten Alor - Hinghar, Heny M. A. (Jurnal Ilmiah Wahana Pendidikan, 2023)
What is meant by village fund accountability is a form of financial accountability carried out by village apparatus in Tribur Village, Abad Selatan District, Alor Regency. Analysis of the Influence of Community Participation on Village Apparatus Competence and Internal Control Systems on Village Fund Management Accountability. This study aims to determine the effect of community participation, village apparatus competence and internal control systems on village fund management accountability. The method in this study uses primary data. The statistical method used in this study is multiple linear regression, while hypothesis testing is carried out using the t test and significant F test. The results of this study indicate that. Participation has an effect on accountability for managing village funds in Tribur Village, Kecematan Abad Selatan, Alor Regency, which has a positive value with a significant level of 0.000. The competence of village officials has an effect on accountability for managing village funds, namely a positive value with a significant level of 0.049. that is, it has a positive value with a significant level of 0.016. Community participation, competence of village apparatus and internal control systems have a simultaneous effect on accountability for village dsna management in Tribur Kecematan ABD Selatan Village, Alor Regency, which together have a significant value of 0.000. or 0%